Development of Counting Box Media to Improve Understanding of Addition and Subtraction of Grade II Elementary School Students - Puspitasari, Aan; Susetyo Kusumo Wardhani, Intan; Puspasari, Yovita (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study was to develop a counting box learning media that will be used to improve the understanding of addition and subtraction of grade II elementary school students that is valid, practical and effective. The type of method in this study is Research and Development (R&D). The product development model is ADDIE. Data collection techniques by conducting interviews, observations, questionnaires and tests. Analysis of research data using data analysis of validity, reliability, discrimination, level of difficulty, normality, homogeneity, hypothesis and effectiveness. The results carried out by the researcher, namely the validity of the counting box media in improving the understanding of addition and subtraction in grade II elementary school students, are suitable for use and have been validated by experts. The results of the validation of media experts were 98% (Very valid), material experts were 95.45% (Very valid), language experts were 91%% (Very valid), and practitioner experts were 95%% (Very Practical). Product trials conducted by researchers were in 2 stages, namely small-scale trials and field-scale trials. The results of the small-scale acquisition of pretest and posttest questions show that the average pretest score is 47.5, while the average posttest score is 55.5. The increase from the pretest to the posttest score is 8. On the field scale, the results of the average pretest score are 40, while the average posttest score increases to 92. So it can be concluded that there is an increase from the pretest to the posttest score of 52. Based on this, the counting box media is very valid, practical and effective to use in learning.